Antecedents and consequences of political moral laxity: a Peruvian case - Agustin Espinosa; Rogger Anaya; Juan Juárez; Huseyin Çakal (Frontiers in Political Science)
Political Moral Laxity is defined as a set of beliefs and attitudes that tolerate and support dishonest or corrupt actions of authorities and politicians, especially when these actions benefit private interests to the detriment of the public good. Political Moral Laxity is the result of perverse political socialisation in political systems characterised by the lack of legitimacy of authorities, the weakening of institutions and, consequently, the non-compliance of citizens. The current study focuses on the mediating role of Political Moral Laxity between Social Dominance Orientation, the components of the Dark Triad of Personality, and Tolerance to Normative Transgression among Peruvian citizens. For this purpose, 242 Peruvian citizens of both genders (male = 45.9%, female = 53.7%, not specified = 0.4%), of legal age (Mage = 20.8, range 18–65), from the region of San Martin in the Peruvian Amazon were surveyed online. Results show that Political Moral Laxity fully mediate the effects of Social Dominance Orientation and only Psychopathy component of the Dark Triad on Tolerance to Normative Transgression. We discuss the results in terms of the Peruvian political system, which is heavily influenced by the neoliberal model, as well as the personality traits that predispose to Political Moral Laxity, thus reinforcing the negative effects of a political model on citizens’ dispositions to transgress.